Audit committee formation in the aftermath of 2007-2009 global financial crisis. - Rezaee, Zabihollah, 1953- (Financial accounting and auditing collection., 2016)
The audit committee, as an integral component of corporate governance, has gained considerable attention in the aftermath of 2007-2009 global financial crisis. The audit committee's role has evolved from a voluntary liaison between management and external auditors to the standing committee of the board of directors in overseeing all aspects of corporate governance, financial reporting, internal controls, risk assessment, and audit activities. This book addresses the determinants of audit committee oversight effectiveness, including their composition, independence, authority, resources, diligence, and activities. Today, audit committees operate in an environment of ever-increasing corporate governance reforms established to protect investors and the public from receiving misleading financial statements and related audit reports. Audit committees, in complying with emerging corporate governance reforms, are striving to improve their oversight effectiveness to discharge their oversight responsibilities. This book is organized into three separate volumes, and each volume can be utilized separately or in an integrated form. The first volume addresses the formation of the audit committee, its relevance, sources, structure and roles; the second volume focuses on the oversight functions of the audit committee; and the third volume presents the emerging issues of audit committees. The first volume consists of five chapters that examine the relevance and fundamentals of the audit committees as well as the determinants of audit committee effectiveness. The second volume consists of nine chapters on financial, auditing, internal control, risk management, ethics and compliance, antifraud, and other oversight functions of the audit committee. The third volume consists of several chapters on the emerging issues of audit committees pertaining to evaluation, education, reporting, and accountability as well as audit committees of private companies, governmental entities, and not-for-profit organizations. The three volumes of this book present the essential and fundamental aspects and functions of audit committees, with a keen focus on their working relationship with other corporate governance participants including the board of directors, executives, internal auditors, external auditors, legal counsel, financial analysts, investment bankers, governing bodies, standard setters, and other stakeholders. Anyone who is involved with corporate governance, the financial reporting process, and audit functions should be interested in this book. Specifically, corporations and their executives, the boards of directors and audit committees, internal and external auditors, accountants, governing bodies, users of financial statements (investors, creditors, pensioners), business schools, and other professionals (attorneys, financial analysts, bankers) will benefit from this book. The three volumes of the book focus on up-to-date corporate governance measures and best practices in the aftermath of the global financial crisis and their impacts on audit committee effectiveness.